Climate and Transformation of Ecosystems by the Example of Natural Plague Foci of South-East of Russia - A. I. Udovikov; N. V. Popov; L. V. Samoilova; S. I. Tolokonnikova (Проблемы особо опасных инфекций, 2012)
Shown was the influence of modern day warming and some other factors on natural plague foci of the European South-East of Russia. Analyzed were the basic mechanisms of transformation of biocenotic structure of natural foci complexes. It was shown that the tendency of gradual change of dominant carriers species would be preserved due to further warming of climate. As a result, the expansion of polyhostal natural foci of plague of semidesert type would be continued.